Student Perceptions of a University Medical Amnesty Policy Are Impacted by Race and Racism: A Qualitative Study. (1st December 2020) - Carroll, Jennifer J.; Mullins, Cameron; Burnham-Lemaire, Georgia; Korycinski, Hannah; Pierce, Hannaleigh; Martinez, Mackenzie; El-Sabawi, Taleed
Abstract: Background: Alcohol consumption on college and university campuses is a public health concern. Some universities have instituted medical amnesty policies (MAPs) to encourage calling first responders to the scene of an alcohol-related emergency. This study describes perceptions of a university MAP and the perceived risks of calling first responders among a sample of undergraduate students at a mid-sized, private, residential university. Methods: This is an exploratory, peer-led study, in which student-researchers worked under faculty supervision to devise the aims of the study, recruit and conduct qualitative interviews with participants, analyze data, and organize major findings. Results: Participants in this convenience sample ( N  = 42) were majority female ( n  = 33, 78.67%) and white ( n  = 35, 83.3%). White students often reported risking disciplinary consequences (i.e. suspension) if found in violation of university alcohol policy. White students who were familiar with the MAP praised it as beneficial in improving student safety. Students of color (especially Black students) reported concerns for their safety in the presence of first responders (especially police officers). Awareness of the MAP among students of color was very low, and many reported low levels of institutional trust, suggesting the protections conferred by the MAP should be taken "with a grain of salt." Conclusions: MAPs may alleviate concern about some perceived risks of calling first responders, but that benefit may not be experienced equitably among students of color. More research is needed to understand the complex relationship between alcohol policies, alcohol-related injuries, policing, and race on college and university campuses.